(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article talks about the reforms that have been carried out in the field of education and its quality improvement and evaluation system in recent years in our country. It is also mentioned about various foreign experiences used in this field and their purpose and importance. In short, it shows how the focus on education has changed in recent years.